2021
DOI: 10.1155/2021/3582342
|View full text |Cite
|
Sign up to set email alerts
|

Dental Pulp Stem Cells on Implant Surface: An In Vitro Study

Abstract: In the field of biology and medicine, one hears often about stem cells and their potential. The dental implant new surfaces, subjected to specific treatments, perform better and allow for quicker healing times and better clinical performance. The purpose of this study is to evaluate from a biological point of view the interaction and cytotoxicity between stem cells derived from dental pulp (DPSCs) and titanium surfaces. Through the creation of complex cells/implant, this study is aimed at analyzing the cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 69 publications
2
20
0
Order By: Relevance
“…The results have confirmed the positive effects of poly-L-lysine on osteoinduction [20,21,28,42,53] and demonstrated a novel potential role also in promoting epithelial cell growth. It means that in clinical practice, a poly-L-lysine topic administration on the surgical mucosal site of a dental implant, could promote, accelerate, and ameliorate the formation of epithelial tissue around semi-submerged and on submerged implants, to favor more rapid healing of the surgical site after the fixture placement and to reinforce the epithelium surrounding the abutment during the remaining life of the implant, thus preventing mucositis and peri-implantitis arising from a loose gingival-implant thigh contact.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The results have confirmed the positive effects of poly-L-lysine on osteoinduction [20,21,28,42,53] and demonstrated a novel potential role also in promoting epithelial cell growth. It means that in clinical practice, a poly-L-lysine topic administration on the surgical mucosal site of a dental implant, could promote, accelerate, and ameliorate the formation of epithelial tissue around semi-submerged and on submerged implants, to favor more rapid healing of the surgical site after the fixture placement and to reinforce the epithelium surrounding the abutment during the remaining life of the implant, thus preventing mucositis and peri-implantitis arising from a loose gingival-implant thigh contact.…”
Section: Discussionsupporting
confidence: 62%
“…Different studies have reported the osteogenic effects of poly-L-lysine on dentalderived stem cells [22][23][24] and their involvement in bone-implant osteointegration [25][26][27][28]. In 2011, Galli et al [20] described the potential mechanisms by which poly-L-lysine can enhance osteogenesis, thus reporting that hMSCs (human mesenchymal stem cells) and hDPSCs cultured on poly-L-lysine-treated titanium (Ti6Al4V) showed significantly higher expression of bone marker genes, produced a higher quantity of calcium deposits, and showed higher cell viability after 12 h of culture in comparison with the cells on the untreated titanium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility to obtain the ligament-anchored implants or implants surrounded by periodontal tissue is the gold standard in the dental surgery. The study in the dental implant field has led to a change from smooth machined surfaces to roughened surfaces in order to improve osseointegration thanks to the osteoconductive and osteoinductive properties [ 9 ]. The characteristics of the implant surfaces have different implications in the integration that it will be possible to achieve with both hard and soft tissues during rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, results of western blotting indicated the increased protein expression of Col I, OPN, and OCN on FN9-10 ELP -titanium treated hMSCs confirming its osteogenic potential ( Fig 8B ). Recently, Laino L et al conducted to improve the osteogenesis of stem cells by modifying the titanium surface and showed that the Col I expression was increased in early-osteogenesis (matrix deposition) and the expression of BSP and OPN was increased in late-osteogenesis (matrix mineralization) [ 60 ]. Liu Jet al investigated osteoblast differentiation by modifying antibacterial osteogenic peptides on titanium and showed that RUNX2 as one of the master transcription factors enhances the expression of downstream genes (e.g., Col I, OCN, etc.)…”
Section: Discussionmentioning
confidence: 99%